Quality, that complex issue: Collaborative design for quality networked learning in HE - Raffaghelli, Juliana E.; Ghislandi, Patrizia (Proceedings of the International Conference on Networked Learning, 2014)
The definition of quality of networked learning (NWL) has been developed a decade ago by the E-Quality Network (2002); according to it, quality NWL should be achieved by promoting interconnected learning in technologically enhanced learning environments. Since that moment, new concepts that could be connected to the conceptual framework for eQuality emerged, including NWL as complex practice requiring design interventions; the idea of operating in contextualized learning cultures; and the need of thinking on interconnections as reflective, dialogic and inclusive relations. This constitutes today a clear framework for practice and research on quality models in terms of both planning strategies and evaluating impacts; however, the contributions in this sense can be considered fragmentary and scarce. In HE, there is still a long way to go in order to implement quality NWL, as part of a broader picture of quality teaching in HE. Factors linked to this problem are the current institutional culture in HE, that privileges attention on research more than on pedagogical practices; leading to naif pedagogical interventions based on the academics conceptions of good teaching, frequently linked to traditional approaches. In this article the authors contend that to promote quality NWL as part of quality teaching, collaborative design for learning represents an effective strategy. This strategy is denominated "the mediated quality process" on the basis of the theoretical contribution of socio-cultural constructivism as well as the advances of the professional learning.and development field, and of quality in eLearning systems. A case study is introduced, where collaborative processes of designing for learning are explored; specifically, the interactions between the members of an academic staff to improve a blended course, as re-design operation, are analyzed. In such process, the academics negotiate values attached to the pedagogical practices and assumptions about good teaching, as well as the role of NWL within it. In fact, collaboration seems to trigger a number of discussions that support a process of negotiating the own quality perspective on pedagogical practices including NWL. In time, this process lead towards integrated, expanded quality perspective that supports academics engagement within a quality culture. The dimensions of the "mediated quality" identified are hence a) to improve the participants knowledge/understanding of quality NWL in a broader context of quality teaching; b) to experience the new quality principles; c) to analyze/reflect on the quality achieved d) to implement concrete innovations to the own practices according to the jointly achieved quality principles.